The adaptive capacity of lake food webs: from individuals to ecosystems. Issue 1 (10th March 2016) - McMeans, Bailey C.; McCann, Kevin S.; Tunney, Tyler D.; Fisk, Aaron T.; Muir, Andrew M.; Lester, Nigel; Shuter, Brian; Rooney, Neil
Abstract: Aquatic ecosystems support size structured food webs, wherein predator‐prey body sizes span orders of magnitude. As such, these food webs are replete with extremely generalized feeding strategies, especially among the larger bodied, higher trophic position taxa. The movement scale of aquatic organisms also generally increases with body size and trophic position. Together, these body size, mobility, and foraging relationships suggest that organisms lower in the food web generate relatively distinct energetic pathways by feeding over smaller spatial areas. Concurrently, the potential capacity for generalist foraging and spatial coupling of these pathways often increases, on average, moving up the food web toward higher trophic levels. We argue that these attributes make for a food web architecture that is inherently 'adaptive' in its response to environmental conditions. This is because variation in lower trophic level dynamics is dampened by the capacity of predators to flexibly alter their foraging behavior. We argue that empirical, theoretical, and applied research needs to embrace this inherently adaptive architecture if we are to understand the relationship between structure and function in the face of ongoing environmental change. Toward this goal, we discuss empirical patterns in the structure of lake food webs to suggest that ecosystems change consistently, from individual traits to the structure of whole food webs, under changing environmental conditions. We then explore an empirical example to reveal that explicitly unfolding the mechanisms that drive these adaptive responses offers insight into how human‐driven impacts, such as climate change, invasive species, and fisheries harvest, ought to influence ecosystem structure and function (e.g., stability, secondary productivity, maintenance of major energy pathways). We end by arguing that such a directed food web research program promises a powerful across‐scale framework for more effective ecosystem monitoring and management.